ANALISIS KEUNTUNGAN PEDAGANG SAYUR KELILING DI KELURAHAN MALALAYANG SATU TIMUR KECAMATAN MALALAYANG KOTA MANADO - Kogoya, Datius; Katiandagho, Theodora Maulina; Baroleh, Jenny (AGRI-SOSIOEKONOMI, 2022)
The purpose of this research was to determine the profit of vegetable traders in East Malalayang Satu Sub-District, Malalayang District, Manado City. The research period is two months from January 2021 to February 2021. The data used in this study are primary data obtained by direct interviews with vegetable traders and secondary data obtained from the sub-district government. Sampling used the purposive sampling method, or the sampling technique was deliberately chosen to only 3 (three) traders selling their wares around the East Malalayang Satu Sub-District, Malalayang District, Manado City. The data obtained in this study were analyzed using descriptive analysis and presented in tabular form. To find out the income of mobile vegetable traders using income analysis. Based on the results of the study, the profit from selling vegetables by mobile vegetable traders who trade around the East Malalayang Satu Sub-District in one day is an average of Rp. 133.003.